Adjusting to Remote Learning as a Result of COVID-19: Experiences of Students and Teachers in Jamaica - Denise (Ignatianum University Press, 2023)
This qualitative study aims to explore the challenges of remote learning during the COVID-19 pandemic in rural and urban Jamaica, from the perspectives of both students and teachers. Data was collected from 20 teachers and 21 students through virtual and face-to-face interviews, questionnaires, and observations of virtual lessons. While there were more positive impacts of remote learning than negative, challenges such as technical issues, attendance, digital competencies, environmental disturbances, unresponsive students, and physical pain were identified. The problem is that teachers and students are frustrated with the challenges of remote learning and are in need of a solution. The study aims to provide assistance to those facing such difficulties and to contribute to future policy decision-making. The results will be used to produce a report that initiates some level of assistance for students and teachers and informs future policy and decision-makers.